Surface evolution and corrosion behaviour of Cu-doped carbide-reinforced martensitic steels in a sulfuric acid solution - Kenta Yamanaka (Nature Portfolio, 2021)
Abstract Cu-doped martensitic steels (Fe–(13, 16)Cr–3W–2Cu–1C) (mass%) with multiple carbide precipitates were prepared at different quenching temperatures, and their corrosion behaviours were examined by measuring the weight loss during immersion in a 0.5 M H2SO4 solution. Lower weight losses and corrosion rates were obtained for the alloy samples prepared at higher quenching temperatures. Surface Cu enrichment was observed for all specimens with a large fraction of dissolved Cr species. Moreover, quenching from higher temperatures not only reduced the amount of M23C6 carbide but also decreased the local electrochemical potential difference between the carbide phase and the martensitic matrix via enhanced surface Cu accumulation, thus increasing corrosion resistance by suppressing microgalvanic corrosion between the constituent phases. The corrosion behaviour of the studied steels was remarkably different from those of the Cu-doped stainless and low-alloy steels with passive oxide surface films, suggesting the strong effect of multiple carbide precipitates on their corrosion behaviour.